BIOCONTROL POTENTIALS OF SELECTED PLANTS AGAINST SOME POST-HARVEST FUNGAL PATHOGENS OF YAM (DIOSCOREA ROTUNDATA P.) IN LAFIA, NASARAWA STATE, NIGERIA - Sulaiman, Bello; Hayatu, M.; Terna, T, P. (FUDMA Journal of Sciences, 2023)
Ethanolic leaf extracts of Ficus sycomorus, Guiera senegalensis, Khaya senegalensis, Sclerocarya birrea, Azadirachta indica, Jatropha curcas and Tamarindus indica were evaluated for biocontrol potentials against selected post-harvest rot fungi of yam (Dioscorea rotundata) in Lafia, Nasarawa State, Nigeria. Rot fungi were isolated from decayed yam tissues by direct plating method. Pathogenicity test revealed that Aspergillus niger, Aspergillus flavus, Aspergillus fumigatus, Fusarium sp., Rhizoctonia sp., and Mucor sp, induced rots in healthy yam tubers after 10 days of inoculation. Aspergillus niger was the most virulent, causing 18.7% tissue damage in infected yam tissues. All plant extracts showed effective inhibition of radial growths ranging from 89.51% to 93.77% on mycelia of Rhizoctonia sp. and Mucor sp., but all plant extracts showed moderate to effective inhibition ranging from 46.28% to 89.33% on mycelial growth of A. niger, A. flavus, A. fumigatus and Fusarium sp. The most significant fungitoxic effects of the extracts (P< 0.05) were observed with leaf extracts of F. sycomorus, G. senegalensis and A. indica at 10g/ml on all tested fungi. Phytochemical screening of ethanolic leaf extracts revealed the presence of saponins, tannins, flavaniods, alkaloids, and phenols in all evaluated plants except T. indica which showed the presence only of saponins and tannins. The biocontrol potentials of ethanolic leaf extracts of A. indica, F. sycomorus, G. senegalensis, J. curcus, K. senegalensis, S. birrea and T. indica, in the effective growth inhibition of the studied rot fungi is an affirmation of the possibility of incorporating these plant materials in the protection of
Keywords: Biocontrol, Botanicals, Fungi, Post-harvest Rot, Yam